Dominant Obligate Anaerobes Revealed in Lower Respiratory Tract Infection in Horses by 16S rRNA Gene Sequencing - KINOSHITA, Yuta (The Japanese Society of Veterinary Science, 2013)
Obligate anaerobes are important etiological agents in pneumonia or pleuropneumonia in horses, because they are isolated more commonly from ill horses that have died or been euthanized than from those that survive. We performed bacterial identification and antimicrobial susceptibility testing for obligate anaerobes to establish effective antimicrobial therapy. We used 16S rRNA gene sequencing to identify 58 obligate anaerobes and compared the results with those from a phenotypic identification kit. The identification results of 16S rRNA gene sequencing were more reliable than those of the commercial kit. We concluded that genera Bacteroides and Prevotella—especially B. fragilis and P. heparinolytica—are dominant anaerobes in lower respiratory tract infection in horses; these organisms were susceptible to metronidazole, imipenem and clindamycin.